Infeksi HIV : Respon Imun Seluler dan Humoral - Selvy Lavia Putri Pricilla; Aflah Afina Nurdin (Jurnal Biodiversitas dan Bioteknologi, 2024)
HIV stands for Human Immunodeficiency Virus, which as the name suggests damages the human immune system. HIV is the virus that causes Acquired Immunodeficiency Syndrome (AIDS). Since the beginning of the HIV epidemic, many studies have shown that HIV infection directly affects the immune system, from both humoral and cellular immunity aspects. The purpose of this journal is to provide information on the mechanisms of humoral and cellular immune responses in HIV infection. HIV infection directly affects the immune system, from both humoral and cellular immunity aspects. Cellular immunity involves T cells in the identification and destruction of pathogens infected with body cells. Cellular components interact and instruct the adaptive immune response. Complementary humoral immunity and mediators between innate and adaptive immune responses can directly neutralize viruses and modulate pathogen elimination. Humoral immunity is immunity with antibody formation by plasma cells derived from B lymphocytes, as a result of cytokines released by activated CD4 lymphocytes.